2016
DOI: 10.1177/0022427816657385
|View full text |Cite
|
Sign up to set email alerts
|

They Protect Our Homeland but Neglect Our Community

Abstract: Objectives: Terrorism is becoming a priority among police agencies in many Western democracies. Scholars argue that increasing homeland security responsibilities can erode police–community relations, in that people perceive the police as neglecting local crime problems for homeland security concerns. Methods: Using Israel as a case study, we evaluate, through path analyses, whether Israeli Jews who perceive that the Israeli National Police (INP) values homeland security more than its crime responsibilities h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 44 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…This is due, in large part, to the incredible influence of Tom Tyler's (2006) seminal work that argues that when individuals perceive criminal justice officials to be acting in a manner that is polite, honest, and unbiased, they will perceive that official's authority to be legitimate and be more likely to comply with their directives, as well as the law, more generally. This hypothesis has largely withstood the scrutiny of numerous tests in a variety of contexts (Jackson, Bradford, Stanko, et al, 2012;Jonathan-Zamir & Weisburd, 2013;McLean & Wolfe, 2016;Metcalfe et al, 2016;Piquero et al, 2005;Reisig & Bain, 2016;Reisig et al, 2012Reisig et al, , 2014Tankebe, 2013b;Tankebe et al, 2016), with few exceptions (cf., Nagin & Telep, 2017). While important, this focus has unfortunately obscured the role of legal socialization in setting the stage for legitimacy evaluations prior to individuals' interactions with the police.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due, in large part, to the incredible influence of Tom Tyler's (2006) seminal work that argues that when individuals perceive criminal justice officials to be acting in a manner that is polite, honest, and unbiased, they will perceive that official's authority to be legitimate and be more likely to comply with their directives, as well as the law, more generally. This hypothesis has largely withstood the scrutiny of numerous tests in a variety of contexts (Jackson, Bradford, Stanko, et al, 2012;Jonathan-Zamir & Weisburd, 2013;McLean & Wolfe, 2016;Metcalfe et al, 2016;Piquero et al, 2005;Reisig & Bain, 2016;Reisig et al, 2012Reisig et al, , 2014Tankebe, 2013b;Tankebe et al, 2016), with few exceptions (cf., Nagin & Telep, 2017). While important, this focus has unfortunately obscured the role of legal socialization in setting the stage for legitimacy evaluations prior to individuals' interactions with the police.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, police legitimacy evaluations are associated with voluntary compliance with the law (Reisig et al, 2007;Tyler & Jackson, 2014;Murphy et al, 2016;Tankebe et al, 2016; but see Nagin & Telep, 2017;Pina-Sánchez & Brunton-Smith, 2020). The effect of legitimacy on compliance tends to be quite generalizable as it has been found in various countries (Jackson, Bradford, Stanko, et al, 2012;Jonathan-Zamir & Weisburd, 2013;Metcalfe et al, 2016;Reisig et al, 2012;Tankebe, 2013b), using different samples (Piquero et al, 2005;Reisig & Bain, 2016;Tankebe et al, 2016), and is robust to potential intervening mechanisms (McLean & Wolfe, 2016;Reisig et al, 2011).…”
Section: Legal Socializationmentioning
confidence: 94%
See 1 more Smart Citation
“…Relatedly, police spending too much time on certain "controversial" activities may also be perceived as a boundary violation. Two survey studies from Israel found that police legitimacy evaluations were lower when people felt the police spent too much time focusing on counter-terrorism activities at the detriment of other crime prevention activities (Jonathan-Zamir & Weisburd, 2013;Metcalfe et al, 2016). In sum, concerns regarding procedural injustice and bounded-authority violations appear to have significant and negative impacts on citizens' legal socialization experiences with police, and both appear to trigger negative attitudes and defiance toward police.…”
Section: Legal Socialization Experiences and Attitudes Toward Policementioning
confidence: 99%
“…From Weber to Beetham to Tyler, legitimacy is important because it generates compliance and cooperation (Beetham, 2013;Tyler, 2006b;Weber, 1947;Zelditch, 2006). In the realm of criminal justice, scholars have particularly focused on the potential for legitimacy to increase compliance and cooperation with the police (Hough et al, 2010;Metcalfe et al, 2016;Reisig et al, 2007Reisig et al, , 2012Reisig & Lloyd, 2009;Tankebe, 2013;Tyler & Fagan, 2008). Thus, police legitimacy has played a critical role in calls for police reform as a promising avenue for improving community-relations and reducing the use of force through the promotion of voluntary compliance (President's Task Force on 21st Century Policing, 2015;…”
Section: Reconciling Traditional Legitimacy With Existing Researchmentioning
confidence: 99%